THE MADDEN-JULIAN OSCILLATION (MJO) IMPACT ON SEA SURFACE TEMPERATURE AND CHLOROPHYL-A IN THE MAKASSAR STRAIT - Vista Millina, Ananda
The Madden-Julian Oscillation (MJO) is an intraseasonal phenomenon that occurs due to a pattern of atmospheric circulation and strong convection and its propagation eastward along the equator. Sea parameters can provide a variety of responses to MJO events. The purpose of this study was to see the effect of MJO on sea surface temperature (SST) and chlorophyll-a in the Makassar Strait. The data used include Outgoing Longwave Radiation (OLR), MJO Real-time Multivariate Index (RMM), wind, SST, and chlorophyll-a from 2004 to 2005 with the study area at coordinates 116° – 119.5° East and 3° – 7° south latitude. The data processing method used is descriptive statistics. Three parameters were used to identify MJO events, namely band-pass filter OLR anomaly ? -10 W/m2, RMM index ? 1 for phases 4 and 5, and low-pass filter zonal wind stress ? 0.02 N/m2, and obtained 34 MJO events are active from 2004 to 2022 with a range of events from December to April. The response of the OLR anomaly band-pass filter shows a decrease in value from the inactive phase to the active MJO phase. The response of the zonal wind stress low-pass filter shows an increase in value from the inactive phase to the active MJO phase. The SPL anomaly response to the MJO event decreased from the inactive phase (highest value of 0.734 oC on day -6) to the active MJO phase (lowest value of -0.034 oC on day +11). Then, the response of the chlorophyll-a anomaly to the MJO event increased from the inactive phase (lowest value of -0.017 mg/L on day -7) to the active MJO phase (highest value of 0.025 mg/L on day +8).